Substantiation of the composition of probiotic cosmetic products for the toning of oily skin - Tkachenko, Nataliіa; Vikul, Svitlana; Sevastyanova, Elena; Dets, Nadiya; Honcharuk, Yana (Technology audit and production reserves, 2017)
The efficiency of using lysates of probiotic cultures of lacto- and bifidobacteria in cosmetics is analyzed, the expediency of using live probiotic cultures in natural cosmetics is shown. The efficacy of using illuminated acid whey and hydroalcoholic extracts of medicinal plants with a high content of bioantioxidants with antiseptic effect (in particular, the extract of dried flowers Tagetes patula) is proved to be effective in the composition of cosmetic means for toning the skin. The optimal mass proportions of acid whey, obtained with the use of probiotic cultures of lacto- and bifidobacteria in the composition of the direct bacterial concentrate FD DVS ABT-2, are justified. As well as a water-alcohol extract of dried flowers Tagetes patula (59.98 and 40.02 % respectively) as components of a probiotic cosmetic for toning of oily skin. It has been established that the maximum antioxidant activity (45.6 act. units) and the normalized value of active acidity (4.76 pH units), the probiotic cosmetic for toning of oily skin, has the optimum content of raw ingredients in it. Namely: 59.98 % of the acid whey obtained using probiotic cultures of lacto- and bifidobacteria in the composition of the direct bacterial concentrate FD DVS ABT-2, and 40.02 % of the water-alcohol extract of the dry flowers of Tagetes patula. It is determined that the organoleptic and physicochemical quality indicators of probiotic cosmetic means for toning of oily skin, produced with the use of raw ingredients in the optimal ratio, meet the requirements of DSTU 4093-2002. By the content of ethyl alcohol the developed product can be attributed to cosmetic lotions. Microbiological indices of the developed probiotic cosmetic lotion differ from those in DSTU 4093-2002, therefore, for the introduction of it into production, it is necessary to develop appropriate regulatory documents. It is proved that the developed probiotic cosmetic lotion is natural and safe due to the improved microbiological characteristics. It is established that the strengths of the product are greater than those of the weak, which indicates its competitiveness in the consumer market. Strategic solutions are proposed for the movement of a new cosmetic product and for reducing the impact of weaknesses on its implementation.